Perbandingan Profil Lipid antara Pesepeda dan Sedenter - Ida Ayu, Eka Widiastuti (Faculty of Medicine Universitas Mataram, 2021)
Lipid pro?le describes the varying levels of lipids in the blood, the most commonly reported ones being high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and triglycerides. Cardiorespiratory endurance exercises, such as cycling increased HDL-cholesterol, while triglycerides and LDL-cholesterol levels decreased. The purpose of this study was to compare lipid profile between cyclists and sedentary people. This research is an analytic observational with cross sectional method. The subjects consist of two different group, which were 21 cyclists of 1st group and 21 sedentary people of 2nd group. Lipid profile was measured on subjects that included serum triglycerides, total cholesterol, HDL-cholesterol and LDL-cholesterol levels. Data were analyzed using independent t-test and Mann-Whitney test. The results showed that there were significant differences (p<0.05) of serum triglycerides (p=0.000), total cholesterol (p=0.005), HDL-cholesterol (p=0.000), and LDL-cholesterol (p=0.001) levels between cyclists and sedentary people. Cyclists have a better lipid profile compared to sedentary people.